A responsabilização de pessoas jurídicas por atos de corrupção : análise da (in)efetividade da Lei Anticorrupção (Lei nº 12.846/2013) - Santos, Dielson Claudio dos (2017)
The present study does not deal with corruption itself. The focus of the research is to study the application of the Anti-Corruption Law (ACL) and its reflexes in the main actors involved, legal entities and Public Administration, as a result of the results of conducting Administrative Responsability Processes (ARP), instituted in Articles 8 to 15 of the ACL. The strict liability, administrative and civil, of legal entities for the practice of acts of corruption is an innovation in the Brazilian legal scenario after the publication of Law 12.846/2013. The objective of this study was to identify a sample of the universe of Administrative Responsability Processes established between January 29, 2014 and February 28, 2017, based on the ACL, using an exploratory field study methodology, bibliographic and documentary research. The objective is to know the current stage of the effective application of ACL and to contribute to improve the delivery of public services. Knowledge of data arising from Administrative Responsibility Process decisions (or only from the opening of ARP) will provide subsidies for the formulation of public policies and strategies for the improvement of actions to defend public patrimony. The analysis of the data found indicates a low adhesion of national public entities in the establishment of Administrative Responsability Processes, as well as low timeliness in the submission of a decision on merits in the proceedings instituted. There is also a low registration of information in the National Register of Punished Companies on the sanctions applied, damaging an active transparency and making social control difficult.